Changes in hand and generalised bone mineral density in patients with recent-onset rheumatoid arthritis. Issue 3 (28th March 2008) - Güler-Yüksel, M; Allaart, C F; Goekoop-Ruiterman, Y P M; de Vries-Bouwstra, J K; van Groenendael, J H L M; Mallée, C; de Bois, M H W; Breedveld, F C; Dijkmans, B A C; Lems, W F
Abstract : Objectives: To evaluate changes in bone mineral density (BMD) in the hands, hip and spine after 1 and 2 years of follow-up, in relation to antirheumatic and antiresorptive therapies and disease and demographic variables in patients with recent-onset rheumatoid arthritis (RA). Methods: Changes in BMD measured in metacarpals 2–4 by digital x -ray radiogrammetry and in the hip and spine by dual energy x -ray absorptiometry were assessed at baseline and after 1 and 2 years of follow-up in 218 patients with recent-onset RA from the BeSt study, who received one of four treatment strategies: sequential monotherapy (group 1); step-up combination therapy (group 2); initial combination therapy with tapered high-dose prednisone (group 3); or initial combination therapy with infliximab (group 4). Results: After 1 and 2 years, there was significant BMD loss in all locations, with significantly greater BMD loss in the hands than generalised BMD loss in the hip and spine. Initial combination therapy with prednisone or infliximab were associated with less hand BMD loss compared with initial monotherapy after 1 and 2 years (−0.9 and −1.6%, −0.6 and −1.4%, −1.7 and −3.3%, and −2.6 and −3.6% for group 4–1 after 1 and 2 years, overall p = 0.001 and p = 0.014, respectively). Progression in erosions was independently associated with increased BMD loss both in the hands and hip after 1 year. The use of bisphosphonates protected only against generalised BMD loss in the hip and spine. Conclusions: The association between joint damage progression and both hand and generalised BMD loss in RA suggests common pathways between these processes, with hand BMD loss occurring earlier in the disease course than generalised BMD loss.